From Popularity to Spirituality: The Da'wah Narrative of Celebrity Hijrah in Television Media - Miftah Fadhil Muragmi (Jurnal Dakwah, 2024)
The concept of hijrah (spiritual migration) has evolved into a popular phenomenon within contemporary Muslim society. As a term currently undergoing a contestation of meanings, this study explores how the television program Hijrah on Trans TV constructs the meaning of hijrah. The research focuses on two main questions: (1) How is the meaning of hijrah represented denotatively and connotatively in six selected episodes of the show? (2) How does Trans TV construct and communicate the message of hijrah through this program? Using a qualitative method with an interpretive content analysis approach, this study examines selected episodes, particularly Cerita Berhijrah Oki Setiana Dewi, to observe verbal expressions, actions, and visual symbols. The research employs Roland Barthes' semiotic theory, focusing on the layers of denotation and connotation to unpack the construction of meaning within the show. Findings indicate that the connotative meaning of hijrah portrayed in the program emphasizes personal transformation, not only in behavior but also in outward appearance. Men are shown adopting what is perceived as more Islamic clothing, while women are portrayed as achieving hijrah primarily through wearing the hijab. However, the study reveals a narrowing of meaning: while hijrah in its denotative sense refers to a comprehensive transformation in faith, behavior, and personality, the episodes largely highlight external changes. Aspects of moral and spiritual growth are underrepresented, suggesting a media-driven shift in focus toward visual markers of religiosity rather than holistic Islamic transformation.